Secondary battery

By using the active material of a specific particle size range in the positive active material layer, the resistance of the positive electrode is increased, the problem of the depth of the use of silicon compounds in the secondary battery is solved, and the life and cycle characteristics of the battery are improved.

CN119384729APending Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380047137.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-16
Filing Date
2023-10-17
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When the existing secondary batteries contain SiOβ(0<β<2) oxide in the negative electrode active material layer, the depth of use of silicon-based compounds increases at the discharge end, resulting in deterioration of battery life and room temperature cycle characteristics.

Method used

By containing small particulate active materials and average particle size (D50) from a average particle size (D50) to 10 μm in the positive active material layer to 8 μm to 20 μm, the resistance of the positive electrode at the end of the discharge at the end of the discharge is reduced, thereby reducing Negative voltage difference, reducing the depth of the use of silicon compounds.

Benefits of technology

Implement the life of the secondary battery and the characteristics of room temperature, and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384729A_ABST
    Figure CN119384729A_ABST
Patent Text Reader

Abstract

The present specification provides a secondary battery including a positive electrode, a negative electrode, a separator, and an electrolyte, in which the negative electrode includes a negative electrode active material layer containing SiO [beta] (0lt; beta < lt >; the positive electrode includes a positive electrode active material layer, the positive electrode active material layer including a small particle active material having an average particle diameter (D50) of 3 [mu] m to 10 [mu] m and a large particle active material having an average particle diameter (D50) of 8 [mu] m to 20 [mu] m, and the porosity of the positive electrode active material layer is 19% to 23%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0133985 filed in the Korean Intellectual Property Office on October 18, 2022, and Korean Patent Application No. 10-2023-0137406 filed in the Korean Intellectual Property Office on October 16, 2023, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a secondary battery. Background Art

[0003] Secondary batteries are generally used not only in portable devices but also in electric vehicles (EV) or hybrid electric vehicles (HEV) driven by an electric drive source due to their easy application to various products and electrical characteristics such as high energy density.

[0004] Secondary batteries have attracted attention as a new energy source that improves eco-friendliness and energy efficiency due to the major advantages that the use of fossil fuels can be significantly reduced and the use of energy does not generate byproducts.

[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator inserted between the positive electrode and the negative electrode, and an electrolyte. In addition, the positive electrode and the negative electrode may be formed with active material layers each containing a positive electrode active material and a negative electrode active material on a current collector. Generally, for the positive electrode, lithium-containing metal oxides such as LiCoO2 and LiMn2O4 are used as positive electrode active materials, and for the negative electrode, carbon compounds, silicon compounds, or mixtures thereof, etc. are used as negative electrode active materials.

[0006] Recently, in order to develop batteries that allow fast charging and have high energy density, a mixture of a carbon compound such as graphite and a silicon compound is used for the negative electrode. However, when a silicon compound is included, electrode expansion / contraction due to the use of the silicon compound occurs at the end of discharge, resulting in side reactions, which shortens the life of the battery and deteriorates the normal temperature cycle characteristics. Therefore, it is necessary to develop a battery that solves these problems. Summary of the invention

[0007] [Technical issues]

[0008] The present invention is directed to providing a secondary battery which contains SiO in the negative electrode active material layer. β (0<β<2) oxides, but by reducing the silicon compounds (SiO β The introduction of (0<β<2) oxide) has improved battery life and room temperature cycle characteristics.

[0009] However, the technical problems to be solved by the present invention are not limited to the above problems, and those skilled in the art will clearly understand other problems not described from the following description.

[0010] [Technical solution]

[0011] An exemplary embodiment of the present invention provides a secondary battery including a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode includes a negative electrode active material layer, and the negative electrode active material layer includes SiO β (0<β<2) oxide and carbon-based active material, the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises an average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) has a large particle size of 8 μm to 20 μm, and the porosity of the positive electrode active material layer is 19% to 23%.

[0012] [Beneficial Effects]

[0013] The secondary battery of the present invention comprises SiO in the negative electrode active material layer β (0<β<2) oxide, including an average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) is a large particle active material with a size of 8 to 20 μm, thereby increasing the resistance of the positive electrode at the end of discharge. The voltage of the secondary battery is determined by the difference between the positive electrode voltage and the negative electrode voltage. By increasing the resistance of the positive electrode at the end of discharge, the positive electrode voltage is sharply reduced, thereby inducing a relatively small increase in the negative electrode voltage, resulting in silicon compounds (SiO β The use depth of (0<β<2) oxide) is reduced, so that a secondary battery with improved life and room temperature cycle characteristics can be obtained.

[0014] Specifically, when a nickel-based active material in the form of single particles with a high nickel content is used for the positive electrode active material layer in order to increase the energy density and rolling density of the battery and reduce the crushing of the active material, and an active material such as SiO is included in the negative electrode active material layer in order to enable rapid charging, β (0<β<2) When silicon compounds such as oxides are present, the voltage of the negative electrode rises rapidly at the end of discharge, resulting in the silicon compounds (SiO β (0<β<2) oxide) is used excessively (increased usage depth), and the battery life performance deteriorates. In order to improve this, the average particle size (D 50 ) is a small particle active material with an average particle size (D 50) is a large particle active material of 8 μm to 20 μm, thereby allowing fast charging, improving the resistance of the positive electrode, and reducing the silicon compound (SiO β The depth of use of (0<β<2) oxide) can thereby obtain a secondary battery with improved room temperature life. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a graph showing cycle life characteristics measured by performing 0.33C charging and 0.5C discharging at normal temperature on the lithium secondary batteries prepared in Example 1 and Comparative Example 1.

[0016] Figure 2 is a graph showing voltage curves of the three-electrode system secondary batteries prepared in Example 2 and Comparative Example 2 under discharge conditions.

[0017] Figure 3 is a graph showing the measurement results of the cycle-life characteristics of the lithium secondary batteries prepared in Example 1 and Comparative Examples 1 and 3. DETAILED DESCRIPTION

[0018] Hereinafter, the present invention will be described in detail. The following description is intended to help understand the present invention, but does not determine or limit the scope of the present invention.

[0019] In the present specification, when a part is referred to as “comprising” a certain component, this means that the part may further include other components, without excluding other components, unless there is a clear contrary description.

[0020] Throughout this specification, when a component is referred to as being “on” another component, the component may be in direct contact with the other component, or intervening components may also be present.

[0021] It should be understood that the terms or words used throughout the specification should not be interpreted as limited to their ordinary meanings or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the words or terms to best explain the present invention.

[0022] As used herein, the singular forms are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0023] In the present specification, the crystallinity of the structure contained in the positive or negative electrode active material can be confirmed by X-ray diffraction analysis, which can be performed by using an X-ray diffraction (XRD) analyzer (product name: D4-endavor, manufacturer: Bruker), or by appropriately adopting an apparatus used in the art other than the above-mentioned apparatus.

[0024] In the present specification, the presence or absence of an element and the content of the element in the positive electrode or negative electrode active material can be confirmed by ICP analysis. The ICP analysis can be performed by using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300).

[0025] In this specification, the end of discharge refers to a region where the SOC (state of charge) of the full battery is 10% or less.

[0026] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured using laser diffraction. For example, the average particle size (D 50 ) may include dispersing particles of a positive electrode active material in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., HORIBALA-960), irradiating the dispersion with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating an average particle size (D ) corresponding to 50% of the cumulative volume in the measuring device. 50 ).

[0027] In this specification, the term "single particle" is a concept opposite to the secondary particle form composed of tens to hundreds of primary particles, and refers to a particle composed of 10 or less primary particles. Specifically, in the present invention, a single particle may be a single particle composed of one primary particle, or may be a particle form composed of a plurality of primary particles.

[0028] In this specification, the term "primary particle" refers to the smallest unit of a particle recognized when an active material is observed by a scanning electron microscope, and "secondary particle" refers to a secondary structure composed of tens to hundreds of primary particles aggregated.

[0029] In this specification, the expression "particle" refers to a particulate matter having a micron size, and when the particle is magnified and observed, the particle can be identified as a "grain" in the form of a crystal having a size of tens of nanometers. When the grain is further magnified and observed, a separate region in the form of atoms forming a lattice structure in a predetermined direction can be identified, wherein the region is called a "crystal". The size of the particle observed by X-ray diffraction (XRD) is defined as the size of the crystallite. The size of the crystallite can be quantitatively determined according to the Scherrer equation by using XRD data.

[0030] The secondary battery of the present invention is a secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode comprises a negative electrode active material layer, and the negative electrode active material layer comprises SiO β(0<β<2) oxide and a carbon-based active material, the positive electrode comprises a positive electrode active material layer, and the positive electrode active material layer comprises an average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) is a large particle active material of 8μm to 20μm.

[0031] In this specification, when the negative electrode active material layer contains SiO β (0<β<2) oxide, the resistance of the negative electrode rises rapidly at the end of discharge, while the resistance of the positive electrode using a positive electrode material with low resistance characteristics decreases rapidly, so that the difference between the resistance of the negative electrode and the resistance of the positive electrode increases greatly. Therefore, there is a problem that the negative electrode deteriorates rapidly, thereby shortening the life of the battery and deteriorating the normal temperature cycle characteristics. In order to solve this problem, the average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) is a large particle active material with a size of 8 μm to 20 μm, which reduces the rapid decrease in positive electrode resistance, thereby obtaining a battery with improved life and room temperature cycle characteristics.

[0032] <Positive electrode>

[0033] The positive electrode of the present invention comprises a positive electrode active material layer, and the positive electrode active material layer comprises an average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) is a large particle active material with a size of 8 μm to 20 μm, and the porosity of the positive electrode active material layer is 19% to 23%.

[0034] According to another exemplary embodiment of the present invention, the positive electrode active material layer includes an average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) is a large particle active material with a size of 8 μm to 20 μm, and the porosity of the positive electrode active material layer is 19% to 23%.

[0035] According to the exemplary embodiment of the present invention, the small particle active material and the large particle active material each contain 80 mol % or more of nickel relative to the total moles of transition metals excluding lithium.

[0036] In an exemplary embodiment of the present invention, the weight ratio of the small particle active material to the large particle active material (the weight of the small particle active material: the weight of the large particle active material) is 2: 8 to 8: 2. When the content of the large particle active material satisfies the above range, there is an effect of increasing the positive electrode resistance at the end of discharge, and when the content deviates from the above range, it is difficult to control the porosity within an appropriate range due to the crushing of the large particles.

[0037] According to an exemplary embodiment of the present invention, the small particle active material has a single particle form.

[0038] According to another exemplary embodiment of the present invention, the small particle active material has a single particle form in which one or more primary particles are aggregated.

[0039] In an exemplary embodiment of the present invention, the large particle active material has a secondary particle form.

[0040] The small particle active material and the large particle active material may each independently include a lithium composite metal oxide containing lithium and one or more metals such as cobalt, manganese, nickel, or aluminum. More specifically, lithium nickel manganese cobalt oxides (for example, Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc.), lithium nickel cobalt transition metal (M) oxides (for example, Li(Ni) p2 Co q2 Mn r3 M s2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are each independently the atomic fraction of the element, 0 < p2 < 1, 0 < q2 < 1, 0 ≤ r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1), etc.), and may include any one or two or more of these compounds. However, the present invention is not limited thereto.

[0041] In addition to the above-described positive electrode active material layer, the positive electrode may further include a positive electrode current collector. In this case, the positive electrode active material layer is formed on at least one surface of the positive electrode current collector.

[0042] In the positive electrode, the positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to enhance the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as a film, sheet, foil, net, porous body, foam, and non-woven fabric body.

[0043] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder together with the above-mentioned positive electrode active material.

[0044] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the constituted battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal carbon black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., and any one of them or a mixture of two or more thereof may be used.

[0045] In addition, the positive electrode binder is used to improve the bonding between the particles of the positive electrode active material and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one or a mixture of two or more thereof may be used.

[0046] The positive active material layer may be formed by applying a positive electrode slurry including a binder and / or a conductive material together with the above-mentioned small particle active material and large particle active material onto at least one surface of a positive electrode collector, and then drying and rolling it.

[0047] The positive electrode slurry according to the exemplary embodiment of the present invention may further include a solvent for forming the positive electrode slurry. Specifically, in order to promote dispersion of components, the solvent for forming the positive electrode slurry may include methyl pyrrolidone (NMP) or the like.

[0048] In an exemplary embodiment of the present invention, the solid content of the positive electrode slurry may be 20 parts by weight to 85 parts by weight, specifically 30 parts by weight to 80 parts by weight, based on a total of 100 parts by weight of the positive electrode slurry.

[0049] According to an exemplary embodiment of the present invention, the porosity of the positive electrode is 19% to 23%. If the porosity of the positive electrode is less than 19%, side reactions may occur due to the crushing of the positive electrode active material, and sufficient contact with the electrolyte may not be achieved due to excessive filling, which may deteriorate the output characteristics or cycle characteristics of the battery. On the other hand, if the porosity of the positive electrode exceeds 23%, there is a problem of reduced energy density of the battery. In addition to the particle size of the above-mentioned positive electrode active material, the porosity of the positive electrode can also be controlled by the presence or absence of surface modification of the positive electrode active material, the type of binder and solvent, calendering temperature and pressure, etc.

[0050] The porosity can be calculated as (1-(calendering density / electrode true density))*100(%). In this case, the calendering density can be calculated as follows.

[0051] Calendering density: Electrode weight excluding foil after calendering (g) / electrode volume excluding foil (sample area * electrode layer thickness, cm 3 )

[0052] Here, the rolled density is the density of the state before the rolled electrode is placed in a battery and activated (charged or discharged), and therefore has the same meaning as the density of the active material layer of the electrode used to manufacture the electrode assembly or the density of the active material layer of the electrode contained in the battery.

[0053] The volume of the electrode excluding the foil refers to the total volume including the pores in the electrode and is calculated as the product of the unit area of ​​the sample and the thickness of the electrode layer after calendaring.

[0054] The true density of an electrode is the intrinsic density of the electrode active material and can be measured by XRD Rietveld refinement.

[0055] <Negative electrode>

[0056] The negative electrode of the exemplary embodiment of the present invention includes a negative electrode active material layer, and the negative electrode active material layer includes SiO β (0<β<2) oxides and carbon-based active materials.

[0057] In addition to the above-mentioned negative electrode active material layer, the negative electrode may further include a negative electrode current collector. In this case, the negative electrode active material layer is formed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes SiO β (0<β<2) oxide and carbon-based active material. In addition, the negative electrode active material layer may further include a binder and / or a conductive material.

[0058] According to an exemplary embodiment of the present invention, the carbon-based active material may be artificial graphite, natural graphite, carbon black, or the like.

[0059] According to an exemplary embodiment of the present invention, the carbon-based active material can be used without particular limitation, and its representative example can include crystalline carbon, amorphous carbon or a combination thereof. Examples of crystalline carbon can include graphite, such as amorphous, plate-like, flaky, spherical or fibrous natural graphite and artificial graphite, and examples of amorphous carbon can include soft carbon (low temperature sintered carbon), hard carbon, mesophase pitch carbide and sintered coke, etc. Graphite can be natural graphite, artificial graphite or a mixture thereof. Relative to a total of 100 parts by weight of the negative electrode active material contained in the negative electrode active material layer, the content of the carbon-based active material can be more than 60 parts by weight and less than 99 parts by weight.

[0060] According to an exemplary embodiment of the present invention, the negative electrode active material layer may include SiO β (0<β<2) oxide active materials and carbon active materials, and including SiO β (0<β<2) The oxide active material may be a material comprising SiO β (0<β<2) and pore silicon-based composite particles.

[0061] SiO β (0<β<2) corresponds to the matrix in the silicon-based composite particles. SiO β (0<β<2) may be a form containing Si and SiO2, and Si may form a phase. That is, β corresponds to SiO β (0<β<2) is the ratio of the number of O and Si contained in the silicon-based composite particles. β When (0<β<2), the discharge capacity of the secondary battery can be increased.

[0062] The silicon-based composite particles may further include at least one of a Mg compound and a Li compound. The Mg compound and the Li compound may correspond to a matrix in the silicon-based composite particles.

[0063] Mg compounds and / or Li compounds may be present in SiO β (0<β<2) neutralization and / or SiO β (0<β<2) on the surface. The initial efficiency of the battery can be improved by Mg compounds and / or Li compounds.

[0064] The Mg compound may include at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.

[0065] In the exemplary embodiment of the present specification, based on 100 wt % of the total of SiO βActive material of an oxide (0 < β < 2), the content of Mg element can be 0.1 wt% to 20 wt% or 0.1 wt% to 10 wt%. Specifically, the content of Mg element can be 0.5 wt% to 8 wt% or 0.8 wt% to 4 wt%. When the above range is satisfied, the Mg compound can be included in the active material including SiO β in the active material of an oxide (0 < β < 2), so that the volume change of the silicon-based active material during the charge and discharge of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0066] The Li compound can include at least one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate can include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The Li silicide can include Li7Si2. The Li oxide can include Li2O.

[0067] In an exemplary embodiment of the present invention, the Li compound can include the form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate can exist in the silicon-based composite particles in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5, and the amorphous lithium silicate can be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5). However, the present invention is not limited thereto.

[0068] In an exemplary embodiment of this specification, based on the total 100 wt% of the active material including SiO β (0 < β < 2) oxide, the content of Li element can be 0.1 wt% to 20 wt% or 0.1 wt% to 10 wt%. Specifically, the content of Li element can be 0.5 wt% to 8 wt%, more specifically 0.5 wt% to 4 wt%. When the above range is satisfied, the Li compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during the charge and discharge of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0069] The content of Mg element or Li element can be confirmed by ICP analysis. For ICP analysis, a predetermined amount (about 0.01g) of the negative electrode active material is accurately taken, transferred to a platinum crucible, and completely decomposed on a hot plate by adding nitric acid, hydrofluoric acid and sulfuric acid thereto. Then, by using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer 7300), a reference calibration curve is obtained by measuring the intensity of a standard solution prepared using a standard solution (5mg / kg) at the inherent wavelength of the Mg element or Li element. Subsequently, the pretreated sample solution and the blank sample are introduced into the spectrometer, and the actual intensity is calculated by measuring the intensity of each component, the concentration of each component is calculated based on the obtained calibration curve, and then the concentration of the calculated component is converted so that the sum of the concentrations is equal to the theoretical value, and the prepared SiO β (0<β<2) The content of Mg or Li in the active material of the oxide.

[0070] In an exemplary embodiment of the present specification, the carbon layer may be disposed on the surface of the silicon-based composite particles and / or inside the pores. The carbon layer imparts electrical conductivity to the silicon-based composite particles, thereby improving the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material containing the silicon-based composite particles. Based on a total of 100% by weight of the silicon-based composite particles, the total content of the carbon layer may be 5% to 40% by weight.

[0071] In the exemplary embodiment of the present specification, the carbon layer may include at least one of amorphous carbon or crystalline carbon.

[0072] In addition, in the exemplary embodiment of the present invention, based on 100 parts by weight of the negative electrode active material, SiO β The content of (0<β<2) oxide is 1 to 15 parts by weight, preferably 1 to 10 parts by weight, and more preferably 5 to 10 parts by weight. β (0<β<2) When the content of the oxide satisfies the above range, the energy density and battery resistance can be improved, and since the volume expansion occurring during the charge and discharge process is small, an excellent effect in life can also be obtained.

[0073] The negative electrode active material layer may be formed by β The negative electrode slurry of a binder and / or a conductive material together with (0<β<2) oxide and a carbon-based active material is coated on at least one surface of a negative electrode collector, and then dried and rolled to form the negative electrode slurry.

[0074] According to the exemplary embodiment of the present specification, in addition to SiO βIn addition to the (0<β<2) oxide and the carbon-based active material, the negative electrode slurry may further include other negative electrode active materials.

[0075] The negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, for the current collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium or silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used for the current collector. The thickness of the current collector can be 6 μm to 20 μm. However, the thickness of the current collector is not limited thereto.

[0076] The adhesive may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0077] There is no particular limitation on the conductive material as long as it has conductivity and does not cause chemical changes in the battery. For example, the following can be used: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbon powders; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and conductive materials such as polyphenylene derivatives, etc.

[0078] The negative electrode slurry may further include a thickener such as sodium carboxymethyl cellulose (Na-CMC), lithium carboxymethyl cellulose (Li-CMC), and cellulose nanofiber (CNF).

[0079] The negative electrode slurry of the exemplary embodiment of the present invention may further include a solvent for forming the negative electrode slurry. Specifically, the solvent for forming the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropanol, specifically distilled water, in terms of promoting dispersion of components.

[0080] In an exemplary embodiment of the present invention, the solid content of the negative electrode slurry may be 20 parts by weight to 75 parts by weight, specifically 30 parts by weight to 70 parts by weight, based on a total of 100 parts by weight of the negative electrode slurry.

[0081] <Secondary Battery>

[0082] The secondary battery of the exemplary embodiment of the present invention may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode and the negative electrode have been described above, a detailed description is omitted.

[0083] The separator is used to separate the negative electrode from the positive electrode and provide a migration path for lithium ions, wherein any separator can be used without particular limitation, as long as it is generally used as a separator in a secondary battery, in particular, a separator having high moisture retention capacity for the electrolyte and low resistance to the migration of electrolyte ions can be preferably used. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or a laminated structure having more than two layers thereof. In addition, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics formed of high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0084] Examples of the electrolyte may include an organic-based liquid electrolyte, an inorganic-based liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that can be used to manufacture a lithium secondary battery, but are not limited thereto.

[0085] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0086] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.

[0087] In particular, among carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates are high viscosity organic solvents, and can be preferably used because they have a high dielectric constant and thus dissociate lithium salts well, and such cyclic carbonates can be mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constants such as dimethyl carbonate or diethyl carbonate and used to prepare an electrolyte having high conductivity, and can be more preferably used.

[0088] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in a non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0089] In addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, increasing the discharge capacity of the battery, etc., for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0090] Another exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include a secondary battery having high capacity and high life and cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large-sized equipment selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0091] Hereinafter, preferred embodiments will be provided in order to better understand the present invention. It will be apparent to those skilled in the art that embodiments are provided only to illustrate the present invention, and various modifications and changes can be made within the scope and technical spirit of the present invention. Such modifications and changes naturally fall within the scope of the claims included herein.

[0092] Example

[0093] <Preparation of battery cells>

[0094] Example 1

[0095] As the positive electrode active material, the average particle size (D 50 ) is 10 μm and the Ni content is 87 mol% NCMA large particle positive electrode material and the average particle size (D 50 ) with a NCM single-particle positive electrode material of 5 μm and a Ni content of 86 mol% was mixed in a weight ratio of 5:5, and the positive electrode active material, CNT as a conductive material, acrylate as a dispersant, and PVdF as a binder were added to methyl pyrrolidone (NMP) as a solvent in a weight ratio of 97:1:0.4:1.6 to prepare a positive electrode slurry.

[0096] Subsequently, the cathode slurry was coated / dried on one surface of an aluminum current collector having a thickness of 12 μm by using a slot die, and then rolled using a roll pressing method, thereby preparing a cathode having a porosity of 22% and a thickness of 125.6 μm.

[0097] A mixture of artificial graphite, natural graphite and SiO2 (70 wt %: 22 wt %: 8 wt %) as negative electrode active materials, carbon black and CNT as conductive materials, SBR as a binder, and CMC as a thickener were added to distilled water as a solvent at a weight ratio of 95: 1: 2: 3 to prepare a negative electrode slurry. The negative electrode slurry was coated on a copper current collector with a thickness of 6 μm, and then dried and rolled under the same conditions as the positive electrode to prepare a negative electrode.

[0098] A non-aqueous electrolyte was prepared in which tetravinylsilane, ethylene sulfate, 1,3-propylene sultone, lithium difluorophosphate and LiBF4 as additives were mixed in an organic solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed in a composition of 30:70 (volume ratio), and 1.0M LiPF6 was dissolved.

[0099] The lithium secondary battery was prepared by inserting a stability enhancing separator (SRS, 12 μm) between the positive and negative electrodes and then injecting an electrolyte.

[0100] Example 2

[0101] The lithium secondary battery with a three-electrode system was prepared by the following process: the positive electrode of Example 1 was punched into a size of 3 cm×4 cm, the negative electrode was punched into a size of 3.1 cm×4.1 cm to form a positive electrode and a negative electrode, and the separator of Example 1 - LTO (Li4Ti5O 12 ) wire-separator, and then injected with a diluted electrolyte. The LTO wire was prepared and used as a reference electrode by coating a copper wire with a slurry made by adding LTO as an active material, carbon black as a conductive material, and PVdF as a binder in a weight ratio of 38.2:2.7:59.1 to NMP as a solvent, and then drying it at 130°C.

[0102] Comparative Example 1

[0103] In addition to using 86% Ni content and an average particle size (D 50 ) was used as the positive electrode material, a lithium secondary battery with a positive electrode porosity of 22% was prepared in the same manner as in Example 1.

[0104] Comparative Example 2

[0105] In addition to using 86% Ni content and an average particle size (D 50 ) was used as the positive electrode material, a lithium secondary battery with a positive electrode porosity of 22% was prepared in the same manner as in Example 2.

[0106] Comparative Example 3

[0107] The positive electrode material having the same composition as Example 1 was rolled in a rolling process to have an increased electrode thickness of 132.2 μm compared to Example 1, thereby obtaining a positive electrode material having a porosity of 26% and preparing a lithium secondary battery in the same manner as Example 1.

[0108] Figure 1 : is a graph showing the cycle life characteristics measured by charging the lithium secondary batteries prepared in Example 1 and Comparative Example 1 at room temperature at 0.33C and discharging at 0.5C. When charging the battery, the charging is set to start in CC mode and then change to CV mode so that the charging is terminated at 4.2V and 0.05C. When discharging the battery, the discharge is set to be terminated at 2.8V in CC mode. Figure 1 It can be confirmed that the life characteristics of the lithium secondary battery prepared in Example 1 are improved compared with the lithium secondary battery prepared in Comparative Example 1. Figure 1 In the figure, the mixed positive electrode 5:5 shows the figure of Example 1, and the single crystal positive electrode 100% shows the figure of Comparative Example 1.

[0109] Figure 2 is a graph showing the voltage curves of the three-electrode system secondary batteries prepared in Example 2 and Comparative Example 2 under discharge conditions. Figure 2 In the figure, the first one from the left shows the voltage of the secondary battery, the second one shows the voltage of the positive electrode, and the third one shows the voltage of the negative electrode. Based on the voltage of the secondary battery, discharge is performed at 0.33C in CC mode until 2.5V. Figure 2 It can be seen from the positive electrode voltage curve in that at the end of discharge, the voltage of Example 2 drops faster than that of Comparative Example 2, and since the negative electrodes of Example 2 and Comparative Example 2 are the same, the positive electrode of Example 2 has a relatively high resistance at the end of discharge. The voltage of a secondary battery is determined by the voltage difference between the positive electrode and the negative electrode. Therefore, it can be seen in Example 2 that due to the decrease in the positive electrode voltage, the increase in the negative electrode voltage at the end of discharge is suppressed, and thus, the silicon compound (SiO β (0<β<2) oxide) is used at a lower depth. Figure 2 In the figure, the mixed positive electrode 5:5 shows the figure of Example 2, and the single crystal positive electrode 100% shows the figure of Comparative Example 2.

[0110] Figure 3 : is a graph showing the cycle life characteristics measured by charging the lithium secondary batteries prepared in Example 1 and Comparative Examples 1 and 3 at room temperature at 0.33C and discharging at 0.5C. When charging the battery, the charging is set to start in CC mode and then change to CV mode so that the charging is terminated at 4.2V and 0.05C. When discharging the battery, the discharge is set to be terminated at 2.5V in CC mode. Figure 3 It can be confirmed that the lithium secondary battery prepared in Comparative Example 3 has inferior life characteristics compared with the lithium secondary battery prepared in Example 1.

[0111] exist Figure 3 In the figure, the mixed positive electrode 5:5p22% shows the graph of Example 1, the single crystal positive electrode 100% shows the graph of Comparative Example 1, and the mixed positive electrode 5:5p26% shows the graph of Comparative Example 3.

Claims

1. A secondary battery comprising: positive electrode; negative electrode; Diaphragm; and Electrolytes, Wherein, the negative electrode comprises a negative electrode active material layer, Wherein, the negative electrode active material layer comprises SiO β (0<β<2) oxides and carbon-based active materials, Wherein, the positive electrode comprises a positive electrode active material layer, Wherein, the positive electrode active material layer comprises an average particle size (D 50 ) is a small particle active material with an average particle size (D 50 ) is a large particle active material of 8 μm to 20 μm, and The porosity of the positive electrode active material layer is 19% to 23%.

2. The secondary battery according to claim 1, wherein The small-particle active material and the large-particle active material each contain 80 mol % or more of nickel relative to the total moles of transition metals excluding lithium.

3. The secondary battery according to claim 1, wherein The small particle active material has a single particle form.

4. The secondary battery according to claim 1, wherein Based on 100 parts by weight of the negative electrode active material of the negative electrode active material layer, the SiO β The content of (0<β<2) oxide is 1 to 15 parts by weight.

5. The secondary battery according to claim 1, wherein The weight ratio of the small-particle active material to the large-particle active material, that is, the weight of the small-particle active material: the weight of the large-particle active material, is 2:8 to 8:2.

Citation Information

Patent Citations

  • Cathode active material, method of preparing the cathode material, cathode, and lithium secondary battery including the same

    CN104282903A

  • Mixed positive electrode active material, positive electrode comprising same, and secondary battery

    CN107078281A

  • Lithium ion secondary battery and method for manufacturing same

    CN109690859A

  • Lithium secondary battery and method for manufacturing same

    CN113273014A

  • Secondary battery

    CN113646946A